Prevalence of Physical Activity and Sedentary Behaviors by Metropolitan Status in 4th-, 8th-, and 11th-Grade Students in Texas, 2004-2005 - Springer, Andrew E. (Centers for Disease Control and Prevention, 2008)
INTRODUCTION: Research on geographic differences in children's physical activity (PA) engagement is limited. This study examined the prevalence of PA and sedentary behaviors in a probability sample of children in the 4th (mean age, 9.7 years; n = 7,907), 8th (mean age, 13.7 years; n = 8,827), and 11th (mean age 16.9 years; n = 6,456) grades by urban, suburban, and rural location in Texas. METHODS: Using data from the 2004-2005 School Physical Activity and Nutrition (SPAN) study, we conducted logistic regression analyses stratified by sex to assess associations of 6 PA indicators and 2 sedentary behavior indicators with metropolitan status. RESULTS: Urban 8th- and 11th-grade students reported the lowest prevalence of PA. Suburban or rural schools were significantly more likely than their urban counterparts to report higher school-based sports team participation in 8th graders (P = .001); higher vigorous PA (P = .01) and strengthening exercise (P = .01) in 11th-grade boys; and higher physical education attendance in 4th (P < .01) and 11th graders (P = .05). Sports team (P = .04) and other organized PA participation (P = .04) in urban 4th-grade girls and vigorous PA in urban 8th-grade boys (P = .04) were the only behaviors for which a significantly higher prevalence was reported compared with nonurban counterparts. We observed few significant geographic differences in prevalence of television watching and video game playing. CONCLUSION: Several significant differences in PA behaviors were found by metropolitan status in this sample of public school students in Texas. Research is needed on availability of PA opportunities and PA barriers by metropolitan status to better understand the lower prevalence estimates reported in older urban children.